Modifying spin current filtering and magnetoresistance in a molecular spintronic device. Issue 72 (12th December 2018) - Zhao, Guo-Dong; Li, Li-Meng; Wang, Yin; Stroppa, Alessandro; Zhang, Ji-Hua; Ren, Wei
Abstract : Three general factors of the molecule device were investigated to enhance its spin filtering efficiency. Abstract : The zigzag edged graphene nanoribbon (ZGNR) is excellent for spintronics devices, and many efforts have been made to investigate its properties such as spin filtering, rectification and magnetoresistance. Here we propose a molecular spintronic transport device based on two ZGNR electrodes connected with a dibenzo[ a, c ]dibenzo[5, 6:7, 8]quinoxalino[2, 3- i ]phenazine (DDQP) molecule. By performing first-principles electron transport computations, we found an enhanced spin polarized current–voltage curve, giant spin filter efficiency, magnetoresistance and rectification ratio properties of the device compared to its all-carbon molecular analogue. Our systematic investigation suggests the vital role played in spin polarized electron transport by nitrogen atoms in DDQP, the ZGNR probe's width and terminal geometry, especially the increased spin filter efficiency with higher ZGNR width.